"Between the straits": Jewish immigration to the United States and Palestine, 1915–1925. Issue 2 (4th May 2017) - Alroey, Gur
ABSTRACT: From 1919 to 1925, some 400, 000 Jews from Eastern Europe emigrated to the United States and Palestine. The central thesis of this article is that the profile of the Jewish exodus before World War I differed from the postwar flow. Above all, Jews who had escaped the carnage of the Ukrainian Civil War (1918–1920) were more akin to refugees than immigrants. The first of this article's three parts revolves around Jewish emigration during World War I via Siberia to Vladivostok or to the Chinese town of Harbin, whereupon they continued to the port of Yokohama and sailed to the US Pacific coast. The second part focuses on new immigration policies that were rolled out by the authorities in the United States and Palestine between 1921 and 1924. Lastly, the third part delves into comparative and demographic aspects of Jewish migration during the 1920s.